2014
DOI: 10.1515/jpm-2014-0073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of depth on shear-wave elastography estimated in the internal and external cervical os during pregnancy

Abstract: Aim To investigate the effect of depth on cervical shear-wave elastography. Methods Shear-wave elastography was applied to estimate the velocity of propagation of the acoustic force impulse (shear-wave) in the cervix of 154 pregnant women at 11-36 weeks of gestation. Shear-wave speed (SWS) was evaluated in cross-sectional views of the internal and external cervical os in five regions of interest: anterior, posterior, lateral right, lateral left, and endocervix. Distance from the center of the US transducer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 59 publications
5
45
1
Order By: Relevance
“…Although they are far from being perfect from a theoretical point of view, evidence from a few published studies suggests that reproducibility of elastographic estimates obtained with the above-mentioned scoring methods is quite satisfactory 23,26,27. This implies that irrespective of the type of equipment, elastographic method, measurement and scoring strategy, elastography produces reliable and comparable results (Table 1).…”
Section: Assessment Of Elastographymentioning
confidence: 99%
“…Although they are far from being perfect from a theoretical point of view, evidence from a few published studies suggests that reproducibility of elastographic estimates obtained with the above-mentioned scoring methods is quite satisfactory 23,26,27. This implies that irrespective of the type of equipment, elastographic method, measurement and scoring strategy, elastography produces reliable and comparable results (Table 1).…”
Section: Assessment Of Elastographymentioning
confidence: 99%
“…It has been used in the examination of breast, thyroid and liver masses and for measuring cervix elasticity, placental insufficiency and in studying the myometrium during labor [27–29]. SWE uses acoustic radiation to generate a shear wave which is a cone-shaped force that is measured using high velocity ultrasound at around 5000 to 20,000 KHz [28]. This measurement of the shear wave, also known as Shear Wave Speed (SWS), is then estimated by software in meters per second and is faster in hard or stiff tissue and slower in softer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This measurement of the shear wave, also known as Shear Wave Speed (SWS), is then estimated by software in meters per second and is faster in hard or stiff tissue and slower in softer tissues. SWE has been used to evaluate the cervix, finding differences in the shear wave speed between cervixes of differing lengths and after treatment with prostaglandins for cervical ripening [28]. The placenta has been examined as well to examine the elastic modulus of the placenta in comparison to other established measures of placental perfusion and is found to have potential for measurement of placental function [27].…”
Section: Discussionmentioning
confidence: 99%
“…38 The cervix, as compared to these tissues, is heterogeneous, and a further complication is that its viscosity dramatically changes during pregnancy, but still the technique appears to be more reliable than strain elastography if data are carefully acquired and interpreted. 3941 Two cross-sectional studies using shear wave elasticity imaging techniques on commercially available systems in pregnant women showed promise, but logistics limited clinical usefulness in one of them 42 and measurement variability was prohibitively large in the other. 43 Another feasibility study in pregnant women at term demonstrated better reliability, but required a prototype transducer (with a linear array with the ultrasound waves parallel to each other instead of the traditional curvilinear endocavity array in which the waves are more complicated) for correct data interpretation.…”
Section: A Timeless Frustration: Cervical Evaluation Is Imprecisementioning
confidence: 99%